PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN BERKUNGJUNG WISATA KE KEBUN RAYA CIBODAS - Wahyudi Ilham (JURNAL MANAJEMEN KULINER, 2022)
According to the result of research performed by the researcher of promotional strategy. Cibodas Botanical Garden manager try to attract the tourist to visit the garden by emphasizing cooperation with schools and giving discount for the visitors (Sales Promotion), distributing brochures and billboard/banner (Advertising), providing website and online media (Direct Marketing) and relying on the tourists who have already familiar with the Cibodas Botanical Garden. The researcher used quantitative method. Types of Descriptive and verificative research were also used to discuss the problem further by selecting the tourists visiting Cibodas Botanical Garden in 2016, which are also treated as research sample. Data was collected by distributing questionnaire to the samples selected by frame sampling. Next, the collected data was processed by SPSS 22.0 program where hypothesis testing was conducted by regression analysis because the researcher aims at finding the correlation among variables and the effects of X1, X2, X3, X4 variables on Y variable. The result of hypothesis testing simultaneously shows that value of Fcount > Ftable, then H0 is rejected and Ha is accepted, which means there is a significant effect simultaneously from the promotional mix (X variable) on visiting decision (Y). Partially, there are several factors affecting visiting decision, which are advertising, personal selling, sales promotion, and direct marketing. Based on the research result, it is suggested that the company improve the supervision of employee work under the leadership in order to achieve better employee productivity.